DIRECT AND INDIRECT EFFECT OF FIRM SIZE AND FINANCIAL PERFORMANCE ON VALUE OF THE FIRM WITH GCG AS INTERVENING VARIABLE IN BUMN - Novi Yanti; Danyl Mallisza; Ivonne Ayesha (Journal of Social and Economics Research, 2022)
The purpose of this study was to determine the effect of firm size and financial performance through GCG on value of the firm both directly and indirectly. This research was conducted at state-owned companies listed on the Indonesia Stock Exchange from 2012-2017. The population used in this study is the financial statements of BUMN companies listed on the Indonesia Stock Exchange (IDX) for the period 2012-2017. The number of BUMN companies listed on the Indonesia Stock Exchange is 20 companies. So the total population in this study is 120 BUMN financial statements for 6 years. The number of companies sampled in this study were 14 companies during the study period, from 2012-2017 using the purposive sampling method. The analytical method used is path analysis, coefficient of determination and hypothesis testing. The results of hypothesis testing and path analysis show that firm size has a positive and significant effect on corporate governance and negative effect on value of the firm partially. Financial performance has a positive and not significant effect on GCG but has a significant effect on value of the firm. While GCG does not affect the value of the company either directly or indirectly.